Association between metabolic risk markers, body composition and different manifestations of strength in young adults (2018)
Introduction: For decades, low levels of muscle strength (MS) have been associated with an increased risk of mortality from all causes. Objective: To identify the correlation between values of different manifestations of MS and metabolic risk markers (MRM) in young university students. Materials and methods: The study included 50 participants (37 men, 13 women), aged between 19 and 23 years. The grip strength of both hands and the muscular strength of upper and lower limbs were evaluated, as well as height, weight, body mass index (BMI), skin folds, HDL, cholesterol and triglycerides. Results: No significant associations between MRM and the different manifestations of MS were found. Conclusion: MS and MRM are separately associated with mortality risk factors and with suffering from cardiovascular diseases. © 2018, Universidad Nacional de Colombia. All rights reserved.